2000
DOI: 10.1088/0741-3335/42/7/302
|View full text |Cite
|
Sign up to set email alerts
|

RF current drive by electron cyclotron waves in the presence of magnetic islands

Abstract: The influence of the presence of magnetic islands, and the consequent modification of the tokamak magnetic surface topology, on electron cyclotron current drive is analysed. To this end, a new three-dimensional Fokker-Planck code has been developed, taking into account the modifications of the magnetic equilibrium topology owing to the presence of the islands. Significant differences between the electron cyclotron current drive efficiency with and without islands inside the plasma are found, particularly in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…For example, under some conditions, the cross-field heat conductivity has been found to be strongly reduced inside the island [30,31]. Theoretical and numerical works have shown that the different magnetic topologies due to the presence of a magnetic island can have important consequences for the flux-surface averaged quasilinear diffusion and the consequent power density deposition profile as well as drive current density profile [32][33][34]. These points will be the subject of future work.…”
Section: Discussionmentioning
confidence: 91%
“…For example, under some conditions, the cross-field heat conductivity has been found to be strongly reduced inside the island [30,31]. Theoretical and numerical works have shown that the different magnetic topologies due to the presence of a magnetic island can have important consequences for the flux-surface averaged quasilinear diffusion and the consequent power density deposition profile as well as drive current density profile [32][33][34]. These points will be the subject of future work.…”
Section: Discussionmentioning
confidence: 91%
“…For cases where the NTM is suppressed using ECCD aimed at the resonant q surface, the changes in the current profile that stabilize the magnetic island are also found from the MSE measurements. (Note that the possible effect of the magnetic island on the ECCD profile [11,12] is not considered in this paper.) In these H-mode plasmas heated primarily by co-current neutral beam injection (NBI), the magnetic island rotation frequency (10-30 kHz) is much faster than the MSE (no aliasing) bandwidth (1 kHz), so only the time-averaged (i.e.…”
Section: Spatiotemporal Changes In Pressure-driven Currents From Ntmmentioning
confidence: 99%
“…B y = δB y cos ky. (11) Perturbations in the toroidal magnetic field are negligible and are not considered. For a tearing mode located at radius r s with poloidal mode number m, periodicity requires k = m/r s .…”
Section: Direct Analysis Of Mse Signals Including Helical Perturbatiomentioning
confidence: 99%
“…We take for the tearing-mode structure a fundamental linear mode with ψ = δψ cos ky. The standard linear tearing-mode picture has magnetic field perturbations of B x = δB x sin ky, (10) B y = δB y cos ky. (11) Perturbations in the toroidal magnetic field are negligible and are not considered. For a tearing mode located at radius r s with poloidal mode number m, periodicity requires k = m/r s .…”
Section: Direct Analysis Of Mse Signals Including Helical Perturbatio...mentioning
confidence: 99%